Depression and Quality of Life in People with Systemic Lupus Erythematosus - Fitria Maharani Harsono Putri; Magdalena S. Halim (ANIMA Indonesian Psychological Journal, 2018)
The aim of this research was to determine the relationship between depression and some aspects of the quality of life. As additional data, the researchers sought connections between demographic factors and the quality of life. This research used measurement implements in the form of the Beck Depression Inventory-II (BDI-II) and the LupusQoL. The participants involved in the research were 49 females aged between 18 and 45 years. The results of the research indicated that depression has a significant relationship with all aspects of quality of life, with the exception of the aspect of body image. The greater the depression, the worse the quality of life. Conversely, the lighter the depression, the better the quality of life. Besides this, the research also indicated a significant difference in aspects of the quality of life, on the basis of demographic factors. The conclusion from the research is that depression is an important matter for attention. By overcoming depression, a number of aspects of the quality of life of people with Lupus/SLE may be improved.